THE TRADITION OF TAHLILAN (THE PRAY FOR THE DEAD): IS IT A LOCAL CULTURE? - Anwar Salafuddin (LP3M Universitas Sains Al Qur'an, 2021)
This article discusses the tradition of Tahlilan in Indonesian which has always been the pros and cons. some people claim that Tahlilan is a Hindu and Buddhist heritage and it does not originate from Islam. This research shows that Tahlilan is not a local Javanese product and Hindu and Buddhist heritage but itcomes from the Middle East, especially Yemen, which is the land of the Walisongo ancestors, where the Walisongo were spreader Islam in Indonesia. Tahlil and the ritual of praying for the dead is a Sunni tradition and it is carried out in several countries such as Egypt, Morocco and Yemen. To analyze this problem the author adjusts to the historical approach. The data are taken from media, books and research results related to the tradition of Tahlilan.